Inhibition of Radiation and Temozolomide-Induced Invadopodia Activity in Glioma Cells Using FDA-Approved Drugs - Clarissa A. Whitehead; Hong P.T. Nguyen; Andrew P. Morokoff; Rodney B. Luwor; Lucia Paradiso; Andrew H. Kaye; Theo Mantamadiotis; Stanley S. Stylli (Translational Oncology, 2018)
The most common primary central nervous system tumor in adults is the glioblastoma multiforme (GBM). The highly invasive nature of GBM cells is a significant factor resulting in the inevitable tumor recurrence and poor patient prognosis. Tumor cells utilize structures known as invadopodia to faciliate their invasive phenotype. In this study, utilizing an array of techniques, including gelatin matrix degradation assays, we show that GBM cell lines can form functional gelatin matrix degrading invadopodia and secrete matrix metalloproteinase 2 (MMP-2), a known invadopodia-associated matrix-degrading enzyme. Furthermore, these cellular activities were augmented in cells that survived radiotherapy and temozolomide treatment, indicating that surviving cells may possess a more invasive phenotype posttherapy. We performed a screen of FDA-approved agents not previously used for treating GBM patients with the aim of investigating their “anti-invadopodia” and cytotoxic effects in GBM cell lines and identified a number that reduced cell viability, as well as agents which also reduced invadopodia activity. Importantly, two of these, pacilitaxel and vinorelbine tartrate, reduced radiation/temozolomide-induced invadopodia activity. Our data demonstrate the value of testing previously approved drugs (repurposing) as potential adjuvant agents for the treatment of GBM patients to reduce invadopodia activity, inhibit GBM cell invasion, and potentially improve patient outcome.